Medios de comunicación radiales y cultura deportiva - Martínez Pesantez, Fernando Vicente (2021)
This research analyzes the sports programs of Radio Sucre in order to identify the reasons why Ecuador lacks a deficit of sports culture in disciplines that are not taken into account. The project has three chapters where the problem is raised, the causes are sought and then solutions are proposed to the problem that affects the sports programs of Radio Sucre and in general the radio communication media of Guayaquil. The methodologies used were applied basic research, documentary research, inductive method, and qualitative all these tools that allowed to obtain a result. At the same time, the surveys and interviews were essential to identify the problems lacking in sports culture in Ecuador.............